Exploring the potential of ChatGPT in facilitating consciousness-raising tasks: A promising solution for alleviating the burden on educators - Tran, Tan (Technology in Language Teaching & Learning, 2024)
When studying grammar, students must not only focus on its structure but also on its form. Form-focused activities are integral to this process, requiring students to identify and manipulate language forms. A well-established technique for facilitating language acquisition is the consciousness-raising task (CR), which aims to heighten learners' awareness of language form. By prioritizing the language input, students can cultivate a more precise comprehension of grammar structures, thereby enhancing their own language proficiency. This approach entails various strategies, such as inferring grammatical rules from examples, comparing different forms of expression, and examining differences between a learner's usage of a grammar item and that of native speakers. However, designing effective CR tasks is cognitively demanding, time-intensive, and laborious for teachers, as it entails accommodating numerous requirements, including the definition of clear objectives, task relevance, and task engagement. To address these challenges, it is worth utilizing ChatGPT which is an advanced conversational AI system with the capability to process and generate various modalities of language. It has access to extensive databases and can produce written content that is frequently indistinguishable from human-written text. Accordingly, ChatGPT can be utilized to generate CR tasks or materials that may be applied in class. The present study endeavors to offer a range of CR tasks for grammar teaching that have been generated by ChatGPT. The tasks include identification tasks, text correction tasks, word choice tasks, and others.